Risk factors affecting outcome of unrelated cord blood transplantation for children with familial haemophagocytic lymphohistiocytosis. (21st November 2018) - Furtado‐Silva, Juliana Montibeller; Paviglianiti, Annalisa; Ruggeri, Annalisa; Boelens, Jaap Jan; Veys, Paul; Ahmari, Ali Abdallah; Zecca, Marco; Locatelli, Franco; Michel, Gerard; Volt, Fernanda; Kenzey, Chantal; Sedlacek, Petr; et al.
Summary: Allogeneic haematopoietic stem cell transplantation is still the only available curative option for Familial Haemophagocytic Lymphohistiocytosis (FHLH). Most studies report outcomes after bone marrow or peripheral blood stem cell transplantation. We analysed the outcomes of 118 children with FHLH undergoing single‐unit umbilical cord blood transplantation performed from 1996 to 2014. Myeloablative conditioning regimen was given to 90% of the patients, and was mostly busulfan‐based ( n  = 81, 76%), including anti‐thymocyte globulin or alemtuzumab ( n  = 102, 86%). The cumulative incidence of Day 60 neutrophil engraftment was 85%; and that of non‐relapse mortality and acute graft‐versus‐host disease (GvHD) was 21% and 33% at 100 days, respectively. The 6‐year cumulative incidence of chronic GvHD was 17% and the 6‐year probability of overall survival was 55%. In multivariate analysis, children receiving a graft with a total nucleated cell dose greater than 9·9 × 10 7 /kg had a better overall survival (hazard ratio [HR]: 0·49, 95% CI: 0·27–0·88, P =  0 · 02). Degree of human leucocyte antigen (HLA) matching was associated with improved disease‐free survival (5/6 vs. 6/6 HR: 2·11, 95% confidence interval [CI]: 1·01–4·4, P =  0 · 05 and ≤4/6 vs. 6/6, HR: 2·82, CI: 1·27–6·23, P =  0 · 01). Umbilical cord blood transplantation with a high cell dose and good HLA match is a suitable alternative option to haematopoietic stem cell transplantation in children with FHLH who lack a HLA‐matched donor.